The Effect Of Sbar Communication On Nurse Attitude In Increasing Patient Safety In Krmt Wongsonegoro Hospital, Semarang - Sembiring, Melyala Cristy; Lestari Ramadhani Nasution, Sri; Girsang, Ermi (International Journal of Health and Pharmaceutical (IJHP), 2022)
Background: WHO officially published the Nine Life Saving Patient Safety, which one is correct communication during handover using the SBAR method. SBAR is considered a clear sign and secure method of communication for problem solving among various disciplines in the medical environment and a simple way of sharing patient information with other medical professionals. Objective: to determine the effect of SBAR communication on the attitudes of nurses in improving patient safety. Methods: This research is a quasi-experimental study with a pretest-posttest design with control group design, the results of the research were processed using paired sample t-test. The data collection of this research uses a checklist of observation sheets to assess the ability attitudes of nurses to communicate SBAR using a questionnaire. Results: this study showed a significant difference in the attitudes of nurses in improving patient safety after being given SBAR communication materials with p-value < 0.05. Conclusion: This study showed significant differences in the attitudes of nurses after being given SBAR communication training in the intervention group. Meanwhile, the control group showed a non-significant difference. This showed that SBAR communication materials affect the attitudes of nurses in improving patient safety.